Associations of Alcohol Consumption With Epigenome‐Wide DNA Methylation and Epigenetic Age Acceleration: Individual‐Level and Co‐twin Comparison Analyses. (30th December 2020) - Stephenson, Mallory; Bollepalli, Sailalitha; Cazaly, Emma; Salvatore, Jessica E.; Barr, Peter; Rose, Richard J.; Dick, Danielle; Kaprio, Jaakko; Ollikainen, Miina
Abstract : Background: DNA methylation may play a role in the progression from normative to problematic drinking and underlie adverse health outcomes associated with alcohol misuse. We examined the association between alcohol consumption and DNA methylation patterns using 3 approaches: a conventional epigenome‐wide association study (EWAS); a co‐twin comparison design, which controls for genetic and environmental influences that twins share; and a regression of age acceleration, defined as a discrepancy between chronological age and DNA methylation age, on alcohol consumption. Methods: Participants came from the Finnish Twin Cohorts (FinnTwin12/FinnTwin16; N = 1, 004; 55% female; average age = 23 years). Individuals reported the number of alcoholic beverages consumed in the past week, and epigenome‐wide DNA methylation was assessed in whole blood using the Infinium HumanMethylation450 BeadChip. Results: In the EWAS, alcohol consumption was significantly related to methylation at 24 CpG sites. When evaluating whether differences between twin siblings (185 monozygotic pairs) in alcohol consumption predicted differences in DNA methylation, co‐twin comparisons replicated 4 CpG sites from the EWAS and identified 23 additional sites. However, when we examined qualitative differences in drinking patterns between twins (heavy drinker vs. light drinker/abstainer or moderate drinker vs. abstainer; 44 pairs), methylation patterns did not significantly differ within twin pairs. Finally, individuals who reported higher alcohol consumption also exhibited greater age acceleration, though results were no longer significant after controlling for genetic and environmental influences shared by co‐twins. Conclusions: Our analyses offer insight into the associations between epigenetic variation and levels of alcohol consumption in young adulthood. Abstract : We used multiple approaches, including an epigenome‐wide association study (EWAS), co‐twin comparisons, and age acceleration analyses, to investigate DNA methylation patterns associated with alcohol consumption within a sample of Finnish twins. Our analyses emphasize the utility of co‐twin comparisons as a complementary approach to EWAS when developing a blood‐based biomarker for alcohol consumption. The co‐twin comparison design enables stronger inferences not possible in samples of unrelated individuals and differentiates valuable biomarkers from markers of correlated genetic or environmental liability.